The Effect of Calcium Oxide and Aluminum Sulfate on Iron, Manganese and Color Removal at Peat Water Treatment - Dedy Mulyadi; Sri Haryati; Muhammad Said (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
The availability of clean water is a basic need for human life. Peat water is well-known as acidic water (low pH), high content of Fe2+ and Mn2+ and colored that make it hard to remove by conventional filtration method. Treatment in batch and continuous methods by using Calcium Oxide (CaO) and aluminum sulfate Al2 (SO4)3×18H2O result in significance reduce of iron and manganese. The batch method in particular, able to reduce iron from 3.5 ppm to 0.1 ppm (97%), manganese from 0.59 ppm to null (100%) and color from 130 TCU to 1.7 TCU. Turbidity also reduced from 33.8 NTU to 1.9 NTU whereas pH increase from 3.19 to 6.8. The continuous method in different circumstances shows iron removal from 3.35 ppm to 0.05 ppm (98.6%), manganese from 0.5 ppm to null (100%) whilst pH raised from 3.19 to 7.16 and turbidity decrease from 31.8 NTU to 1.14 NTU. Both results fulfill the water quality standard required by Permenkes No. 416/Menkes/1990